Implementasi Media Pembelajaran Interaktif dalam Mendukung Pemahaman Siswa Kelas VI Sekolah Dasar Tentang Masa Pubertas - Srikandhi, Naomi; Hasanah, Uswatun; Kurniawati, Wahyu; Husna, Anisya Al (Indo-MathEdu Intellectuals Journal, 2024)
This study investigates how interactive learning media can help students in sixth grade elementary school understand puberty. Puberty, which is an important phase in a child's development, is very important to have a good understanding of the physical and emotional changes that occur. To gain a better understanding of students' experiences and perceptions when using interactive learning media, subjective qualitative research with a phenomenological approach was used. Data was collected through active observation during the learning process and comprehensive interviews with sixth grade students at an elementary school. The focus of the interviews was students' experiences when using interactive learning media and how this impacted their understanding of puberty. Thematic analysis was used to analyze the data to find main themes from the interview and observation data. The research results showed that interactive learning helped students understand puberty. Through interesting visual and audio media, students find it easier to understand the material presented. Because there are interactive elements that make learning more fun, they feel more motivated and interested in learning. Compared with conventional learning approaches, some students prefer to discuss sensitive topics about puberty through interactive media. This research found that interactive learning tools can help sixth grade students understand puberty. It is recommended that schools incorporate interactive learning media into their curriculum